L’implicite et l’interface sémantique-pragmatique : où passe la frontière ? - Jacques Moeschler (Corela)
The semantics-pragmatics interface issue appeared at the beginning of the Gricean turn, based on the concepts of non-natural meaning and implicature. The main issue is the criteria defining linguistic meaning from intended speaker’s meaning. In this article, we give empirical arguments enlightening the complexity of the semantics-pragmatics interface, as generalized conversational implicatures, explicatures, or the relation between truth-conditions and pragmatic meaning. We mainly discuss four types of content, semantic (entailment, presupposition) and pragmatic (explicature, implicature) ones, by showing that the explicitness and negation criteria give a first answer to the semantics-pragmatics interface issue. Additional criteria (truth-conditionality, speaker’s commitment, context, implicitness) give a precise picture of the complexity of linguistic and pragmatic meanings, originating the conceptual and procedural meaning distinction (Moeschler 2016a) and explaining the sinuous shape of the semantics-pragmatics border (Moeschler to appear).